PENGARUH GAYA HIDUP, LITERASI, SIKAP, DAN LINGKUNGAN SOSIAL TERHADAP MANAJEMEN KEUANGAN(studi pada istri pelayaran di desa lajing kecamatan arosbaya) - Iftitah sr, Nurul; Dawam, Aulia (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This research is entitled "The Influence of Lifestyle, Literacy, Attitudes and Social Environment on Financial Management (study of shipping wives in Lajing village, Arosbaya subdistrict).This research was created to determine the influence of lifestyle, literacy, attitudes and social environment on financial management (study of shipping wives in Lajing village, Arosbaya subdistrict) from an economic financial perspective. The independent variables in this research are lifestyle, literacy, attitudes and social environment. The population in this study were all shipping wives in Lajing village, Arosbaya subdistrict. The sample in this study used convenience sampling. Convenience sampling is a sample to obtain information quickly, cheaply and easily. Convenience sampling is often used. The sample was chosen because it was considered suitable for the research and could provide the information needed so there were 95 people sailing in Lajing village. The data collection technique used in this research is by observation, questionnaire and bibliography, while the data analysis technique in this research is the quantitative influence technique. The results of this research show that lifestyle and literacy simultaneously have a positive and significant effect on financial management. Meanwhile, attitudes and social environment simultaneously do not have a positive and significant influence on financial management.